Liquidity-driven FDI - Ron Alquist; Rahul Mukherjee; Linda L. Tesar (Graduate Institute of International and Development Studies, 2014)
We develop a model of foreign direct investment (FDI) in which financially liquid foreign firms acquire liquidity-constrained target firms. Using a large dataset of emerging-market acquisitions, we find evidence supporting three central predictions of the model: (i) firms in external finance dependent and intangible sectors are more likely to be targets of foreign acquisitions; (ii) these targets have ownership structures with larger foreign stakes; (iii) these effects are most prominent in countries with low levels of financial development. The regression evidence indicates that liquidity is at least as economically important as technology- or trade-related motives for FDI in emerging-market economies.
Keywords: F21; F23; G34; L24; L60; 330; foreign direct investment; cross-border mergers and acquisitions; financial development; external finance dependence; asset tangibility; emerging markets